Voices from the classroom dimensions of good teaching - Davis, Diane, direction; Crawford, James T. (Santa Monica, California : Pyramid, 1993)
This video brings to life the concepts relevant to excellence in teaching and should be a welcome addition to any faculty orientation and / or faculty development program
Graphics, Bill Johnston
Narrator: Ted Sohier
Keywords: Teaching -- Technique; Classroom environment